1999
DOI: 10.1042/bj3450099
|View full text |Cite
|
Sign up to set email alerts
|

Two zebrafish (Danio rerio) antizymes with different expression and activities

Abstract: Cellular polyamines are regulated by a unique feedback mechanism involving ornithine decarboxylase (ODC) antizyme. The synthesis of mammalian antizyme requires a programmed translational frameshift event induced by polyamines. Antizyme represses ODC, a key enzyme for polyamine synthesis, through accelerating enzyme degradation by the 26 S proteasome. Antizyme also inhibits the cellular uptake of polyamines. In the present study we isolated two distinct zebrafish (Danio rerio) antizyme cDNA clones (AZS and AZL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The ornithine concentration can be sufficient to supply polyamine synthesis during the development, since the maintenance of the cell polyamine concentration for growing, proliferation (Pilz et al 1990) and DNA synthesis is dependent on it and is altered by the concentration of its precursor, ornithine (Byus and Wu 1991). The ODC gene is housekeeping, and the putrescine production is regulated by polyamine levels in the ODC translation (Matsufuji et al 1996, Saito et al 2000. The ornithine concentration to polyamine synthesis can be directly affected by OCT activity.…”
Section: Discussionmentioning
confidence: 98%
“…The ornithine concentration can be sufficient to supply polyamine synthesis during the development, since the maintenance of the cell polyamine concentration for growing, proliferation (Pilz et al 1990) and DNA synthesis is dependent on it and is altered by the concentration of its precursor, ornithine (Byus and Wu 1991). The ODC gene is housekeeping, and the putrescine production is regulated by polyamine levels in the ODC translation (Matsufuji et al 1996, Saito et al 2000. The ornithine concentration to polyamine synthesis can be directly affected by OCT activity.…”
Section: Discussionmentioning
confidence: 98%
“…A lot of attention has recently been focused on AZ, because of its unique regulation by translational frameshifting. Thus far, the only study on embryonal Az/AZ expression in vertebrates has been performed on 24-h zebrafish embryos (Saito et al, 2000). Using whole-mount in situ hybridization it was demonstrated that Az mRNA is expressed in every tissue of the zebrafish embryo, but predominantly in the central nervous system and in the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…VSa13 and VSa16 cultures were initiated at 22C in L-15, a medium well suited for supporting cell growth in non-CO 2 -equilibrated environments and widely used to culture fish cells (Bols et al 1994;Chi et al 1999;Fernandez et al 1993;Ganassin et al 1999;Saito et al 2000;Tong et al 1997). In this medium, both cell types exhibited a spindle-like phenotype and a slow growth rate and were unable to mineralize their ECM.…”
Section: Development Of Bone-derived Cell Lines From Teleost Fishmentioning
confidence: 99%